Avoiding extinction: equal treatment of the present and the future - Graciela Chichilnisky (Economics: The Open-Access, Open-Assessment E-Journal, 2009)
Equal treatment for the present and the future was required in two axioms introduced in the articles by Chichilnisky of the years 1996 and 1997. These articles provide a characterization of the decision criterion that satisfies the axioms and shows that the two axioms are equivalent to physical limits in the long-run future. The author proves that maximizing discounted utility with a long-run survival constraint is equivalent to maximizing a criterion that treats equally the present and the future. The equal treatment axioms are therefore the essence of sustainable development. The weight given to the long-run future is here identified with the marginal utility of the environmental asset along a path that narrowly misses extinction. An existence theorem is also provided for optimizing according to the welfare criterion that treats equally the present and the future. The author shows that no prior welfare criteria satisfy the axioms for sustainable development introduced in her article of the year 1996.
Keywords: H43; Q51; Q54; 330; Sustainable development; sustainable preferences; axioms for sustainable development; long-run discounting; dictatorship of the present and the future; extinction; equal treatment for the present and the future; long-run optimization; Zeitpräferenz; Soziale Diskontrate; Nachhaltige Entwicklung; Optimales Wachstum; Erschöpfbare Ressourcen; Theorie